Zastosowanie terapii integracji sensorycznej jako formy wsparcia małego dziecka - Dobrowolski, Tomasz (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
Working with young children, we must bear in mind their multilateral development needs. Currently, in kindergartens there are a lot of pupils with various disorders. Recently, there is a significant increase of those who need sensory integration therapy. In the following study, I present the process of conducting the aforementioned therapy and present practical solutions aimed at developing communication skills.